PROMEPROS: um processo de melhoria de processos de software: um processo de melhoria de processos de software - Cassia Rodrigues de Carvalho Ferreira Leite (2010)
This dissertation presents a contextualization of a work originally developed by the author, together with other employees, in order to attend the software company need of creating a process for improving the software development process, according to the process capability and maturity model defined by SEI - CMMI-DEV. The objective pursued by the company was developing a process that supports continuous and systematic improvement of its software development process. The process should cover the technical, managerial, environmental and quality disciplines related to structured work of planning, design, implementation and delivery of improvements in the software development process. As part of the process development, it was first decided to determine how the software company was strategically and tactically acting to enhance their processes. Based on the result obtained and on the company objectives, a new process for improving the software development process was created with similar structure and approach of the organization's software development process, segmented into phases and disciplines.The main contributions of this dissertation were the evaluations of ProMeProS and its development methodology, considering the literature researches conducted after the work completion in the target organization. The results of these evaluations were considered for proposing future works of ProMeProS evolution.